The use of peppermint (Mentha piperita) leaves meal reduces ammonia excreta, increases egg production, and egg quality of laying hens - Asril Adjis; Rizal Tantu; Sri Sarjuni; Jihan Aditia Dwi Putri; Rizky Kumalasari; Burhanudin Sundu; Ummiani Hatta (Faculty of Animal Science, Universitas Brawijaya, 2022)
A study was carried out to determine the effect of peppermint (Mentha piperita) leaves meal on ammonia production, dry matter excreta, egg production, and the quality of laying hens. A total of 80 laying hens of Lohmann Strain aged 20 weeks old were used as experimental animals. The birds were allocated in individual battery pens. The 20-week-old laying hens were vaccinated for New Castle diseases protection by using VaksimuneÂ®ND B1on day 5 after arrival. The hens were kept for 8 weeks and fed four experimental diets. The diets used were basal diet (BSL), basal + 1% peppermint leaves meal (PLM) (BSL+1PLM), basal + 2% PLM (BSL+2PLM) and basal + 3% PLM (BSL + 3PLM). Feed and drinking water were present at all times. Parameters measured were ammonia concentration, dry matter excreta, hen day production, total egg mass, feed intake, FCR, dry matter digestibility, and quality of 14-days-stored eggs. A completely randomized design with 4 experimental diets and 5 replications was used. Data collected from this study were analyzed by using analysis of variance and tested with the Tukey test. The addition of peppermint leaf meal reduced ammonia production and increases dry matter excreta, total egg mass production, and dry matter digestibility. The Haugh unit, yolk height, and albumen height were improved when the eggs were kept for 14 days at room temperature. The addition of peppermint leaves meal decreased the mass loss of 14 days-stored eggs. In conclusion, supplementation of diets with peppermint leaf meal decreased ammonia concentration and watery excreta and increased the quality of eggs stored for 14 days at room temperature.